PERSEPSI SANTRI TERHADAP EKSRAKURIKULER MUSIK RELIGI DI MADRASAH ALIYAH SWASTA AR-RAHMAH DESA AIR MELES ATAS KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Wira Adiyatma; Irdhan Epria Darma Darma; Esy Maestro (FBS Universitas Negeri Padang, 2018)
Abstract This study aimed to describe the students’ perception toward the religious music as extracurricular learning at MAS Ar-Rahmah, Air Meles Atas village, Rejang Lebong Regency, Bengkulu. It was qualitative study using descriptive approach. The object of the study was the students of MAS Ar-Rahmah. The data were obtained by using structured interview, observation and documentation. The result showed that the students of MAS Ar-Rahmah agreed with the existence of the religious music for their extracurricular learning. It can be seen from the average score which was 75.85% while the score range was 61-80 and the alternated answer was ‘agree’.